PERAN KEPALA SEKOLAH DALAM AKTUALISASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) DI SMP BINA MUDA BANYUASIN - Muntazir, M; Saputra, Agus Guntur (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The educational system that has been managed in a bureaucratic and centralized climate is considered one of the causes causing deterioration in the quality and excellence of education in the country. Because bureaucracy always places power as the most decisive factor in the decision-making process. Ironically the principal and the teachers' councils as the one who best understands the reality of education are in a supported place. Though they should be the most role as decision makers in overcoming various daily problems that facing efforts to improve the quality of education. But they are in a position of helplessness and depression with a variety of standardization in the form of operational and technical guidelines. However, with the emergence of regional autonomy, there is also an education reform, in which case policy and decision authority are in school. This is all implemented because education is part of the most important asset to improve the dignity of the nation. School quality improvement management is a transfer of authority and responsibility of education and the community, which the quality improvement process is planned, organized, implemented and self-evaluated by the school in accordance with the school's needs involving all elements associated with the school. One of the parties responsible for the successful improvement of the quality of education in schools is the principal. The progress of a school's retreat depends on the principal because the principal is the key to success in an institution. The principal will be a figure for all the citizens of the school because it is at the forefront and can be measured success. With the enactment of school autonomy, the principal has a significant role in implementing programs already established by the school. Because it is known also, with the school principal kepiafayaan quality will be better. Starting from the thought, the authors are interested to conduct research on: The role of principals in the actualization of MPMBS in SMP Bina Muda Banyuasin. Key words— school-based quality improvement management, Principal, role